Global Warming" in the Perspective of Environmental Management Accounting (EMA) - Damayanti Damayanti; Destia Pentiana (Jurnal Ilmiah ESAI, 2013)
Global warming issue that has been greatly emerged is fully realized by the society, including business society, one of the causes of global warming is excessive nature exploitation done by all of us, including bussiness society. Increased public green awareness has encouraged business to consider environmental effects of their activities and also to take environmental matters into decision making. This paper addresses this concern by discussing environmental management accounting (EMA) as a means to separately identify, quantify, analyse and interpret corporate environmental aspects. EMA techniques for costing analysis, investment evaluation and performance measurement also presented. Keywords : Global warming, environmental management accounting (EMA), Techniques EMA.